CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN REPUTASI PERUSAHAAN DALAM MENINGKATKAN NILAI PERUSAHAAN - Muhammad Al Bukhori; Ersi Sisdianto (CV. KAMPUSA AKADEMIK PUBLISHING, 2025)
This study aims to analyze the relationship between Corporate Social Responsibility (CSR), corporate reputation, and company value. The method used is a qualitative approach through literature study, with secondary data collection from annual reports and academic journals. The results show that companies actively engaged in CSR tend to have better reputations, which positively contributes to company value. Reputation acts as a mediator between CSR and company value, where a good reputation enhances investor and customer trust. This study emphasizes the importance for companies to design relevant and transparent CSR programs, thus strengthening their reputation and achieving long-term sustainability.